1981
DOI: 10.1042/bj1970345
|View full text |Cite
|
Sign up to set email alerts
|

Some properties of the lectin from Datura stramonium (thorn-apple) and the nature of its glycoprotein linkages

Abstract: The lectin from Datura stramonium (thorn-apple; Solanaceae) has been purified by affinity chromatography and shown to be a glycoprotein containing about 40% (w/w) of carbohydrate. The most abundant amino acids are hydroxyproline, cystine, glycine and serine. Results obtained by gel filtration in 6m-guanidinium chloride on Sepharose 4B suggest that it has a subunit mol.wt. of about 30000 and that it probably associates into dimers. The lectin is inhibited specifically by chitin oligosaccharides and bacterial-ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
21
0

Year Published

1983
1983
2001
2001

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(24 citation statements)
references
References 30 publications
(37 reference statements)
3
21
0
Order By: Relevance
“…Noteworthy is the high content of hydroxyproline (=12%) and serine (--10%). These two amino acids serve as attachment points for oligosaccharide chains in cell wall glycopolypeptides of Chlamydomonas (13) and higher plants ( [14][15][16], in plant arabinogalactan proteins (17), and in the wall-associated lectins of the Solanacae (18)(19)(20)(21)(22)(23). Arabinans linked to hydroxyproline in plant cell wall proteins are thought to reinforce the polyproline II helical conformation (24, 25; G. J.…”
Section: And Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Noteworthy is the high content of hydroxyproline (=12%) and serine (--10%). These two amino acids serve as attachment points for oligosaccharide chains in cell wall glycopolypeptides of Chlamydomonas (13) and higher plants ( [14][15][16], in plant arabinogalactan proteins (17), and in the wall-associated lectins of the Solanacae (18)(19)(20)(21)(22)(23). Arabinans linked to hydroxyproline in plant cell wall proteins are thought to reinforce the polyproline II helical conformation (24, 25; G. J.…”
Section: And Discussionmentioning
confidence: 99%
“…The self-assembly of Chlamydomonas wall glycoproteins into a crystalline pseudowall (42) undoubtedly involves molecular recognition, making it attractive to speculate that the sexual agglutinin has evolved from such structural proteins to perform an intercellular recognition or adhesion function. Because plant lectins also contain hydroxyproline-rich domains (18)(19)(20)(21)(22)(23), the Chlamydomonas agglutinin may well also prove to have lectin activity, with its stiff domain 2 serving to display more distal recognition domains to gametes of the opposite mating type. The presence of a collagen-like tail on the asymmetric form of-acetylcholinesterase of vertebrate nervous systems (43) and the crosslinking properties of the collagen IV component of the basal lamina (44) suggest that a similar molecular design may have been adopted more generally by proteins that function to mediate cell-cell interactions.…”
Section: And Discussionmentioning
confidence: 99%
“…The hydroxyproline-rich cell wall glycoprotein from carrot has been shown by circular dichrometry to exist in the polyproline II conformation (17), which consists of a lefthanded helix of three residues per turn and a rise for residue of 0.31 nm (15). Based on optical rotary dispersion measurements, it has been suggested that lectins of the Solanaceae also contain polyproline II conformation (1,7). In was isolated from the medium by affinity chromatography on myeloma protein J539-Sepharose (3).…”
mentioning
confidence: 99%
“…Potato and Datura lectins are poor inhibitors of all the antibodies, consistent with their known low content of i-galactose which is in the a-configuration (2,6).These lectins have a high content of L-arabinose which is mainly present as tri-and tetra-arabinosyl side chains. The anomeric linkages are in the ,-configuration except for the terminal nonreducing arabinosyl group of the tetra arabinosyl side chains which are in the a-configuration (2,6).…”
Section: Resultsmentioning
confidence: 69%
“…The anomeric linkages are in the ,-configuration except for the terminal nonreducing arabinosyl group of the tetra arabinosyl side chains which are in the a-configuration (2,6).…”
Section: Resultsmentioning
confidence: 99%